I hope and I continue - Ding, Yi (Industrial management + data systems, 2018)
Purpose Continued usage of information systems (ISs) is highly critical to a firm’s sustained success. The expectancy-disconfirmation framework has been effective in explaining continuance. However, our own experiences suggest that we may continue using an IS despite low satisfaction. One of the reasons is that the prediction of future user intent in existing models is predominantly retrospective. The purpose of this paper is to address this gap by incorporating forward-looking considerations into the expectancy-disconfirmation model. Design/methodology/approach A questionnaire survey was conducted for two types of mobile applications: photo-sharing and note-taking, and 593 valid responses were collected. The partial least squares method was employed for structural model analysis for each type of applications. Findings The well-entrenched expectancy-disconfirmation model was empirically verified. This study further shows that the influence of satisfaction on continuance intention is higher when hope for the future of a mobile application is stronger, and vice versa, after controlling for the impact of past usage behaviour. In addition, hope is found to be induced by appraisals of perceived usefulness and importance of a mobile application. Originality/value This study demonstrates that the expectancy-disconfirmation model can be enhanced with considerations of future outcomes. It shows that emotions such as hope are inherent to continuance decisions. Moreover, it goes beyond the valence dimension of emotions and identified specific antecedents of hope based on the appraisal theory.